Spontaneous upper eyelid ecchymosis: A rare presenting sign for frontal sinus mucocele. (4th May 2017) - Mehta, Amy A.; Wagner, Lilly H.; Blace, Nancy
ABSTRACT: Paranasal sinus mucoceles are benign lesions that commonly present with orbital signs due to their anatomic proximity. We are reporting a case of bilateral frontal sinus mucocele presenting with spontaneous eyelid ecchymosis. To our knowledge this is the first case report of eyelid ecchymosis as the initial sign of this condition. In addition, our patient lacked commonly described symptoms such as diplopia or pain. This report highlights the importance of including frontal sinus mucocele in the differential diagnosis of spontaneous periorbital ecchymosis.